2017
DOI: 10.1098/rspb.2017.0268
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of climatic niches in squamate reptiles

Abstract: Despite the remarkable diversity found in squamate reptiles, most of their species tend to be found in warm/dry environments, suggesting that climatic requirements played a crucial role in their diversification, yet little is known about the evolution of their climatic niches. In this study, we integrate climatic information associated with the geographical distribution of 1882 squamate species and their phylogenetic relationships to investigate the tempo and mode of climatic niche evolution in squamates, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 52 publications
4
58
0
Order By: Relevance
“…554 Thereby, the evidence of a lack of niche conservatism, and the recent accumulation of 555 ecological diversity could be associated with the possible geographic and climatic isolation 556 throughout speciation, which could promote the rapid accumulation of ecological differences 557 between species of the group (Culumber & Tobler, 2016). This pattern coincides with the 558 results of Pie et al (2017), who found an extensive rate of heterogeneity in climatic niche 559 evolution of squamates with shifts involving accelerations concentrated in its recent 560 evolutionary history. 561 CONCLUSIONS 562 Our results indicate a lack of PNC in the niche evolution of torquatus group with the possible 563 exception of two bioclimatic variables, and only one linked with viviparity.…”
Section: Resultssupporting
confidence: 74%
“…554 Thereby, the evidence of a lack of niche conservatism, and the recent accumulation of 555 ecological diversity could be associated with the possible geographic and climatic isolation 556 throughout speciation, which could promote the rapid accumulation of ecological differences 557 between species of the group (Culumber & Tobler, 2016). This pattern coincides with the 558 results of Pie et al (2017), who found an extensive rate of heterogeneity in climatic niche 559 evolution of squamates with shifts involving accelerations concentrated in its recent 560 evolutionary history. 561 CONCLUSIONS 562 Our results indicate a lack of PNC in the niche evolution of torquatus group with the possible 563 exception of two bioclimatic variables, and only one linked with viviparity.…”
Section: Resultssupporting
confidence: 74%
“…Our study represents, to our knowledge, the first one evaluating the existence of phylogenetic conservatism of climatic niches across the whole turtle clade. Climatic niche conservatism is a well‐studied subject in several vertebrate groups (Duran & Pie, ; Duran et al., ; Mcnyset, ; Peixoto et al., ; Peterson, ; Pie et al., ), but in turtles, it is still poorly explored. The few studies that have evaluated niche conservatism in this group found a mix of evidence for both divergence and conservatism, mainly in the biological invasions scenario (Liu et al., ; Rödder et al., ; Rodrigues, Coelho, & Diniz‐Filho, ; Rodrigues, Coelho, Varela, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although evolutionary patterns of species' climatic niches have been recently evaluated in many taxa (Duran, Meyer, & Pie, 2013;Duran & Pie, 2015;Mcnyset, 2009;Peixoto, Villalobos, & Cianciaruso, 2017;Peterson, 2011;Pie, Campos, Meyer, & Duran, 2017), few studies have tested whether patterns of climatic niche evolution are related to other taxon traits. In mammals, for example, species occurring in the tropics, with small range sizes or with specialized diets have climatic niches that are more conserved than temperate, widely distributed and diet-generalist mammals (Cooper, Freckleton, & Jetz, 2011).…”
mentioning
confidence: 99%
“…Under this hypothesis we expect environmental features that may place the strongest physiological constraints on lizard clades, such as low water availability in arid regions (Cox & Cox, 2015;Neilson, 2002;Pastro, Dickman, & Letnic, 2013), or cold winter temperatures (Aragón, Lobo, Olalla-Tárraga, & Rodríguez, 2010;Pie, Campos, Meyer, & Duran, 2017), to have the greatest effect in suppressing species richness or FD. Across the 10 lizard clades used in this study, this hypothesis receives the greatest support, with a strong effect of temperature in six clades, and relatively weaker effect of aridity in two clades for species richness, and an effect of temperature on four clades, and aridity on two clades for FD.…”
Section: Environmental Filteringmentioning
confidence: 99%